(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Death is one of the significant things to write about because it highlights the value of life. Thus, Albee demonstrates various colours of death. In some plays Albee discusses death in general but Albee’s mastery can be judged through the plays in which Albee portrays the impact of death on the living persons rather than its impact on the person who is dying. Albee not only attacks human being’s inability to face death or death as a medium to release from this absurd world, but also makes a wonderful presentation of death-watch in his plays. This death watch portrays the process of dying along with the presentation of the ritual of waiting and shows us that how this death-watch affects and haunts the life of survivors.